2018
DOI: 10.1002/humu.23386
|View full text |Cite|
|
Sign up to set email alerts
|

MYO5B,STX3, andSTXBP2mutations reveal a common disease mechanism that unifies a subset of congenital diarrheal disorders: A mutation update

Abstract: Microvillus inclusion disease (MVID) is a rare but fatal autosomal recessive congenital diarrheal disorder caused by MYO5B mutations. In 2013, we launched an open‐access registry for MVID patients and their MYO5B mutations (www.mvid-central.org). Since then, additional unique MYO5B mutations have been identified in MVID patients, but also in non‐MVID patients. Animal models have been generated that formally prove the causality between MYO5B and MVID. Importantly, mutations in two other genes, STXBP2 and STX3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 62 publications
7
72
0
Order By: Relevance
“…Notably, enterocytes of patients with MVID also display similar polarity defects to those observed upon V0/vha-1(RNAi), such as the basolateral appearance of microvilli-specific proteins (Wiegerinck et al, 2014) and PAR polarity module components (Michaux et al, 2016) as well as the cytoplasmic displacement of trafficking proteins (i.e. STX3, the SNARE family component SNAP23 and cellubrevin; Dhekne et al, 2018). Finally, MVID has also been associated with enlarged lysosomes displaying a heterogeneous content and with the accumulation of cytoplasmic translucent vesicles (Iancu et al, 2007;Vogel et al, 2016) as well as the specific disorganization of Rab11 + apical recycling endosomes (Vogel et al, 2017a;Talmon et al, 2012), which we also found in V0-ATPase knocked-down worms (Fig.…”
Section: V0-atpase Silencing Phenocopies Microvillus Inclusion Diseasementioning
confidence: 89%
“…Notably, enterocytes of patients with MVID also display similar polarity defects to those observed upon V0/vha-1(RNAi), such as the basolateral appearance of microvilli-specific proteins (Wiegerinck et al, 2014) and PAR polarity module components (Michaux et al, 2016) as well as the cytoplasmic displacement of trafficking proteins (i.e. STX3, the SNARE family component SNAP23 and cellubrevin; Dhekne et al, 2018). Finally, MVID has also been associated with enlarged lysosomes displaying a heterogeneous content and with the accumulation of cytoplasmic translucent vesicles (Iancu et al, 2007;Vogel et al, 2016) as well as the specific disorganization of Rab11 + apical recycling endosomes (Vogel et al, 2017a;Talmon et al, 2012), which we also found in V0-ATPase knocked-down worms (Fig.…”
Section: V0-atpase Silencing Phenocopies Microvillus Inclusion Diseasementioning
confidence: 89%
“…All the other mutations were found in single MVID patients. Finally, 62 different mutations (including the c.1979C>T that is peculiar to Navajos) were found in the MVID patients studied so far . Several of these mutations have a clear pathogenic effect (ie, nonsense, splicing, or frameshift), while 24 were missense.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 62 different mutations (including the c.1979C>T that is peculiar to Navajos) were found in the MVID patients studied so far. 18 Several of these mutations have a clear pathogenic effect (ie, nonsense, splicing, or frameshift), while 24 were missense. We revised 15 of them by using several bioinformatic tools 20 and predicted the pathogenicity (Table S1) in all cases with the exception of the c.1856C>T mutation, which was found in a Dutch patient with MVID that had two other pathogenic mutations (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations